Integrasi Kearifan Lokal dalam Praktik Islam Moderat, Membangun Harmoni Sosial di Era Globalisasi - Dewi, Febriana Kurnia (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The era of globalization is expected to be able to integrate all aspects of human life more easily with the development of technology, especially in the practice of religious moderation. This research aims to analyze the integration of local wisdom in moderate Islamic practices to build social harmony in the era of globalization. The research method used PRISMA 2020 systematic literature review, based on Google Scholar and e-resources of the National Library, 122 articles were found, but only 20 articles were analyzed. The results show that in the current era of globalization, Indonesia is not yet optimal to integrate local wisdom in moderate Islamic practices, and a life of social harmony has not been created comprehensively in Indonesia. Local wisdom and moderate Islamic practices shouldy synergize each other to create moderate social harmony, the role of various stakeholders; tribal leaders, community leaders, governments and communities who participate in each other.